Review on consumers' privacy and economic value acceptance in Smart Grid implementation - Ariffin A.H.; Kaman Z.K. (Seventh Sense Research Group, 2023)
The Smart Grid is a new technology that transforms from a conventional electric grid to an electronically controlled system. Generally, the Smart Grid system consists of generators, distribution and transmission, and consumers. Smart Grid gives enhancement in terms of intelligent de-centralized control which also known as internet of energy, consumer empowerment, and smart infrastructure. There are several studies conducted to understand the social impact, in terms of consumer adoption on the smart grid system. The fundamental issues in the Smart Grid are low of awareness, consumer acceptance, management of data collection, and metering. Therefore, this paper gives a focus to understand the consumers' privacy and economic value challenge in Smart Grid implementation. New security and privacy regulation and policies should be imposed clearly to increase consumer acceptance. Besides, the financial smart partnership between government, private sector and community could expedite the implementation of the smart grid. 2020 Polish Psychological Bulletin. All rights reserved.